A Note on Practical Stability of Nonlinear Vibration Systems with Impulsive Effects - Qishui Zhong; Hongcai Li; Hui Liu; Juebang Yu (Journal of Applied Mathematics)
This paper addresses the issue of vibration characteristics of nonlinear systems with impulsive effects. By utilizing a T-S fuzzy model to represent a nonlinear system, a general strict practical stability criterion is derived for nonlinear impulsive systems.